Sex Tourism (Commercial Sexual Exploitation) on Child Modus Operandi in Batam (Indonesia) and Singapore - sumirat, Jauhar; Nadwa Laga, Mohammad Fatiyo (Sekolah Tinggi Ilmu Kepolisian, 2024)
This paper aims to elucidate the mechanisms through which this crime occurs and persists. This research employs an analysis of Political Economy and Market Analysis, focusing on the impacts of the crime. This study originates from the issue of Commercial Sexual Exploitation of Children (Sex Tourism) between Indonesia and Singapore. This research is a qualitative study that emphasizes a literature review. It employs Political Economic Analysis (PEA) theory and Theories of Change as analytical tools. The findings of this research indicate that the crime discussed in this study is caused by multidimensional factors, including political, economic, and market-driven aspects. Additionally, the impacts of this crime result in damage to institutions, particularly in the political aspects, as well as to individuals and society, affecting social, economic, and physical dimensions. Child sexual tourism crime is a part of CSEC, which is a crime against human rights and human exploitation. There is a need for serious collaboration to address and mitigate this issue.